Quality of Life in End Stage Renal Disease Patients who are Undergoing Hemodialysis - Bai, R. Regi; Rathi, R. K. (Innovational: Journal of Nursing and Healthcare, 2024)
Introduction: Chronic kidney disease and the methods of its treatment play an important part in shaping the patients’ quality of life (QOL) who is receiving hemodialysis. As a result, kidney failure causes many limitations in patients’ physical, mental, and social activities. Aim: This study aims to assess the perceived QOL among End Stage Renal Failure patients who are receiving hemodialysis. Methodology: A descriptive design was adopted with 30 samples who met the inclusion criteria to conduct the study in the hemodialysis unit. The instrument used for the study was the QOL Index-dialysis version. It describes how satisfied you are with the area of your life and how important this treatment for your life. Subjects were asked to rate their level of satisfaction and the level of importance of 34 aspects of life. Results: The QOL was reported to be satisfactory. The subjects were satisfied with most areas of their lives. The total score of health is 53.9 ± 5.26 in view of important areas whereas in the satisfied area it is 53.86 ± 5.01. They did not rate the need to get hemodialysis or receiving a kidney transplant as important. Conclusion: The present study suggests that the QOL of end stage renal disease patients undergoing hemodialysis is considerably impaired compared to that of the healthy subjects